Chemical Composition and Food Safety of Sheep Meat Sate Grilled with Different Time and Fuel - Suryanto, Edi (2014)
The experiment was conducted to evaluate chemical compositions and food safety of sheep meat sate grilled with different time and fuel. Sheep meat was seasoned with spices and then grilled with three duration times (3, 5 and 7 minutes) and two kinds of fuel (gas and charcoal). The data collected were chemical compositions (water, crude protein, soluble protein, fat and collagen contents) and Polycyclic Aromatic Hidrocarbon (PAHs) residual content. The PAHs residual content indicated by benzo(a)pyrene was analyzed using chromatography permeation gel analysis method with descriptive analysis to measure the presence of benzo(a)pyrene residual. The data of chemical composition were statistically analyzed by variance analysis (Completely Randomized Design 3x2 of factorial pattern) and the differences between means were tested by Duncan’s New Multiple Range Test. The results showed that grilling duration decreased significantly the water and soluble protein content of sheep meat sate (P<0.01), whereas crude protein, fat, and collagen contents of sheep meat sate increased. Gas grilling resulted higher water, fat and collagen contents (P<0.01) and soluble protein content (P<0.05) of sheep meat sate than charcoal grilling. There were interaction between grilling duration and kind of fuel on crude protein, soluble protein, fat, and collagen contents. Sheep meat sate grilled with different time and fuel indicated the presence of benzo(a)pyrene residual. It could be concluded that the grilling duration and kind of fuel affected chemical composition of sheep meat sate. The benzo(a)pyrene as contaminant indicator as presence of sheep meat sate.